Perbaikan Sistem Monitoring Sertifikasi Pekerja Berbasis Dashboard Interaktif dengan Metode PDCA - Putri Nabila; Christopher Davito Prabandewa Hertadi (Fakultas Rekayasa dan Teknologi Industri, 2025)
Worker certification is an important aspect in supporting company operations, especially in the oil and gas industry which has high work risks and requires workers with competencies that meet established standards. PT Pertamina Hulu Indonesia Regional 3 Zone 9 needs to ensure that worker certification validity periods are properly monitored so that recertification can be planned on time. The problem identified in this study is that certification monitoring is still carried out manually using Microsoft Excel, which requires data to be checked one by one and increases the risk of overlooking certifications that are approaching their expiration dates. This study aims to apply the Plan-Do-Check-Act (PDCA) method to improve the monitoring system and to design an interactive dashboard to support the control of worker certification data. The data used in this study consisted of historical training and certification records from 2023 to 2025. Data processing was conducted through cleaning, standardization, Master Data preparation, and the addition of supporting columns such as expired date, total day, month, remaining days, status reminder, priority, cost cluster, and training category. The processed data were then developed into dashboards using Microsoft Excel and Power BI. The results show that the designed dashboard can present certification information in a more concise, structured, and understandable format. Microsoft Excel was considered more suitable for daily operational monitoring because it is easy for the Human Capital Business Partner (HCBP) function to use, while Power BI was more effective for reporting needs due to its stronger visual display. The application of PDCA and the design of an interactive dashboard can support a more directed worker certification monitoring process. Keywords: PDCA, dashboard, monitoring, certification, Power BI